A rare case of Ovarian Juvenile Granulosa Cell Tumor in an Infant with Isosexual Pseudo Puberty and a Revision of Literature : A 9-month-old female with ovarian granulosa cell tumor - De Sanctis, Vincenzo; Ahmed, Shayma; Soliman, Ashraf; Alyafei, Fawzia; Alaaraj, Nada; Al Maadheed , Maryam; Clelland, Colin (Acta Biomedica Atenei Parmensis, 2021)
Juvenile ovarian granulosa cell tumors (JGCTs) are described infrequently in pediatrics, and their finding in infants is exceptional. We highlight the presenting symptoms, radiologic images, operative management, and histopathologic findings of a 9-month-old female with isosexual pseudopuberty. An updated revision of literature in infants below the age of 12 months is also reported.